(untitled) (Experimental biology, 2009)
The contact unitary irradiation of rats an infrasound within 3 minutes results to got immunodepressiv syndrome. Unitary introduction of the water irradiated with an infrasound unitary within 3 minutes, results to got immunodepressiv syndrome